Postural Control and Psychophysical State Following of Flight Simulator Session in Novice Pilots - Polak, Ewa; Ślugaj, Remigiusz; Gardzińska, Adrianna (Frontiers in Public Health, 2022)
Flight simulator can cause side effects usually called simulator sickness. Scientific research proves that postural instability can be an indicator of the occurrence of simulator sickness symptoms. This study aims to assess changes of postural control and psychophysical state in novice pilots following of 2-hours exposure to simulator conditions. The postural sway was quantified based on variables describing the displacement of the Centre of Pressure generated in a quiet stance with eyes open (EC) and closed (EC). The psychophysical state was assessed using the Simulator Sickness Questionnaire (SSQ). The research was carried out in a group of 24 novice pilots who performed procedural and emergency flight exercises in the simulator at the Instrument Meteorological Conditions. Each subject was examined twice: immediately before the simulator session (pre-exposure test), and just after the session (post-exposure test). The differences in postural stability between pre- and post-exposure to simulator conditions were assessed based on the normalized Romberg quotients, calculated for individual variables. The lower mean values of all Romberg quotients confirmed the decreasing difference between the measures with eyes open and with eyes closed in the post-exposure tests. After the flight simulator session, the mean values of SP, MA, and SA with EO increased and with EC decreased. The visual contribution to postural sway control was reduced as an adaptive response to the flight simulator environment. The mean values for all SSQ scores (total, nausea, oculomotor, and disorientation scales) were significantly higher in post-exposure tests. The largest increase was noted in the oculomotor SSQ scores (from 9.8 ± 7.2 to 37.9 ± 16.1). Over 50% of pilots participated in this study expressed symptoms typical of simulator sickness connected with visual induction: fatigue, eyestrain, difficulty focusing and difficulty concentrating. The severity of oculomotor and disorientation symptoms were rated as moderate (total SSQ score of more than 25 and less than 60). This study concludes that changes noted in the postural control and psychophysical state of the studied pilots after exposure to the flight simulator confirm the occurrence of the simulator sickness symptoms. Although, we did not find significant correlation postural stability with SSQ scores.